Prediction of minimal residual viremia in HCV type 1 infected patients receiving interferon-based therapy - Viola Knop; Gerlinde Teuber; Hartwig Klinker; Bernd Möller; Jens Rasenack; Holger Hinrichsen; Tilman Gerlach; Ulrich Spengler; Peter Buggisch; Konrad Neumann; Christoph Sarrazin; Stefan Zeuzem; et al. (Annals of Hepatology, 2013)
Introduction. Complete suppression of viral replication is crucial in chronic HCV treatment in order to prevent relapse and resistance development. We wanted to find out which factors influence the period from being already HCV RNA negative by bDNA assay (< 615 lU/mL) to become undetectable by the more sensitive TMA test (< 5.3 lU/mL).Material and methods. Evaluated were 433 HCV type 1-infected patients. All of them received 1.5 ug/kg Peg-IFNa-2b plus ribavirin for 18-48 weeks. bDNA was performed weekly during the first 8 weeks and thereafter at weeks 12, 24, and 48. Patients who became bDNA undetectable were additionally analysed by TMA.Results. Of the 309 patients with on-treatment response (< 615 lU/mL), 289 also reached undetectable HCV RNA levels by TMA. Multivariate analysis revealed that viremia ≤ 400,000 lU/mL (p = 0.001), fast initial virologic decline (p = 0.004) and absence of fibrosis (p = 0.035) were independent predictors of an accelerated on-treatment response by TMA assay in already bDNA negative patients. bDNA negative patients becoming HCV RNA undetectable by TMA within the following 3 weeks had a frequency of relapse of 21%, whereas those showing TMA negativity after 3 weeks relapsed in 38% (p = 0.001). In RVR patients (bDNA < 615 lU/mL at week 4) the corresponding relapse rates were 15.3% vs. 37.5%, respectively (p = 0.003).Conclusion. Early viral kinetics, baseline viremia and fibrosis stage are important tools to predict persistent minimal viremia during interferon-based therapy. The data have implications for designing a more refined treatment strategy in HCV infection, even in the setting of protease inhibitor-based triple treatment.